A revision of the gobiid fish genus Pseudogobius (Teleostei, Gobiidae, Tridentigerinae), with description of seven new species from Australia and South-east Asia - Larson, Helen K.; Hammer, Michael P. (Zootaxa, 2021)
The tridentigerine genus Pseudogobius is widespread, from temperate to tropical areas of the Indo-west Pacific. A morphological review of the genus was carried out, with the initial focus on South-east Asian and Australian species. There are about 21 nominal species in the genus; however, the type specimens for some nominal species are missing. Our work recognises 15 valid species so far, including seven new species, which are described herein: P. aquilonius n. sp., P. cinctus n. sp., P. eos n. sp., P. hoesei n. sp., P. jeffi n. sp., P. rhizophora n. sp. and P. verticalis n. sp. We also conclude that P. poicilosoma (Bleeker, 1849) is the senior synonym of P. javanicus (Bleeker, 1856). Pseudogobius poicilosoma, P. gastrospilos (Bleeker, 1853) and P. javanicus are accepted here as conspecific, although the types are in poor condition (note that all three names were given to specimens collected within close proximity to each other in coastal Java, Indonesia). A key to valid species is presented. The revision benefited from an adaptive feedback loop with companion genetic analyses, with the most comprehensive data available for the Australian region. Broader preliminary genetic data suggest the potential for recognition of additional cryptic species, with the current study providing a platform for future systematic work. Pseudogobius are a prominent part of estuarine biodiversity in the Indo-west Pacific, and this study helps to highlight the need to better understand the taxonomy and conservation requirements of cryptobenthic fishes.